(untitled) (Applied Biological Research, 2024)
Plant-derived pharmaceuticals are gaining increased acceptance in treating various ailments, but ensuring their quality is crucial. Both conventional and modern techniques are employed to validate the quality. High performance thin layer chromatography (HPTLC) and Fourier transform infra-red (FTIR) analysis were conducted to analyse and identify the various phytoconstituents in serial root extract of Holostemma ada-kodien. The peaks observed in HPTLC fingerprint profile corresponding to different phytoconstituents served as markers for standardizing drug; while FTIR analysis aids in identifying the major functional groups present. Thirteen bands were noted for hexane extract of H. ada-kodien in short UV in track I, while chloroform and methanol extracts showed eight bands each. In track II, the hexane extract exhibited eight bands, while chloroform and methanol extracts showed eleven and eight bands, respectively, under similar conditions. The hexane extract in long UV showed a maximum area of 78.4 and 71.59%, in track 1 and 2, respectively, with respective spanning from Rf 0.61 to 0.75 and 0.51 to 0.73. The methanol extract in visible light in track I showed a maximum area of 46.87%, spanning from Rf 0.73 to 0.98, and in track II, it displayed a maximum area of 36.59%, spanning from Rf 0.75 to 0.96 with 10 µL applied. Methanolic root extract of H. ada-kodien showed clear banding patterns in HPTLC fingerprints which seemed to be a dependable technique to detect adulteration while FTIR technique revealed functional groups of methanol root extracts.